Behaviour, Furnishing and Vertical Space Use of Captive Callimico (Callimico goeldii): Implications for Welfare - Amanda Bartlett; Lena Grinsted; Marianne Sarah Freeman (Animals, 2023)
Provision of optimal captive care should be supported by species-specific evidence. Callimico (Callimico goeldii) is a small South American callitrichid primate. This study sought to address gaps in species-specific knowledge and captive management research by examining differences in callimico behaviour across multiple collections, investigating vertical enclosure use and a possible association between specific behaviours and vertical zones. Observational research was conducted at five European Association of Zoos and Aquaria (EAZA) organisations, in exhibits that were visually divided into four vertical zones. Instantaneous scan sampling was used to record behaviour and location of callimico over a six-day period at each collection, exceeding 160 observational hours. Significant differences were observed in foraging between collections and were much lower than the recommendations in Best Practice Guidelines, although near-wild levels were recorded in one enclosure. At an average height of 2 m, callimico utilized a similar vertical space across very different enclosures, regardless of overall available height, reflective of their natural ecology. The association between whole food items and increased foraging time, horizontal branches and locomotion and deep substrate and diversity of behaviours, offers further species-specific evidence of how the callimico use their captive environment. Our findings complement current EAZA guidelines to support species appropriate care for callimico and makes specific recommendations for further research.